2018
DOI: 10.1002/adma.201805557
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoparticle‐Laden Macrophages for Tumor‐Tropic Drug Delivery

Abstract: Macrophages hold great potential in cancer drug delivery because they can sense chemotactic cues and home to tumors with high efficiency. However, it remains a challenge to load large amounts of therapeutics into macrophages without compromising cell functions. Here we report a silica-based drug nanocapsule approach to solve this issue. Our nanocapsule consists of a drug-silica complex filling and a solid silica sheath, and it is designed to minimally release drug molecules in the early hours of cell entry. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
154
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(157 citation statements)
references
References 51 publications
(53 reference statements)
3
154
0
Order By: Relevance
“…Macrophages have been proven as an excellent nanoparticles carrier with small side effects and good tumor targeting. [29][30][31][32] FePd NPs loaded macrophages (FePd@M) can be targeted to the tumor site, which also greatly increased the accumulation of nanoparticles in the tumor site. Compared with the control group and exposed nanoparticles, FePd@M showed a stronger photothermal treatment effect (about 90% of tumors are ablated) and better nuclear magnetic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages have been proven as an excellent nanoparticles carrier with small side effects and good tumor targeting. [29][30][31][32] FePd NPs loaded macrophages (FePd@M) can be targeted to the tumor site, which also greatly increased the accumulation of nanoparticles in the tumor site. Compared with the control group and exposed nanoparticles, FePd@M showed a stronger photothermal treatment effect (about 90% of tumors are ablated) and better nuclear magnetic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing reports on the potential of biomimetic drug carriers, more recent research has been focused on their functionality . Another attractive aspect of the use of cell membranes as surface coatings is the fact that they can effectively inherit proteins or other biologically active molecules from their source and “mimic” the source cells' characteristic activities in vivo .…”
mentioning
confidence: 99%
“…As stated previously, rapid internalization of nanoparticles by macrophages and trafficking to sites of inflammation has led to reports of macrophages functioning as cell-based drug carriers [ 49 , 50 , 51 ]. Zhang et al reported that silica-based nano capsules loaded with doxorubicin can be loaded into macrophages with minimal drug release in the first hours after uptake and minimal effect on in vivo cell migration to tumors [ 52 ]. In further support of targeting macrophages as drug and nanocarriers, here we studied the intercellular transfer of doxorubicin between macrophages using a second macrophage-like cell line, murine J774A.1.…”
Section: Resultsmentioning
confidence: 99%